SYNTHESIS, CHARACTERIZATION AND ADSORPTION TEST OF POLY-TETRA-p-PROPENYLTETRAHYDROXYCALIX[4]ARENE FOR CADMIUM ION - Triana Kusumaningsih; Jumina Jumina; Dwi Siswanta; Mustofa Mustofa; Keisuke Ohto; Hidetaka Kawakita (Universitas Gadjah Mada, 2011)
Synthesis, characterization and adsorption test of poly-tetra-p-propenyl-tetrahydroxycalix[4]arene for cadmium ion had been done. The synthesis was carried out in five steps, which were (1) synthesis of p-t-butylcalix[4]arene from p-t-butylphenol, (2) debutylation of p-t-butylcalix[4]arene, (3) tetraallylation of 25, 26, 27, 28 tetrahydroxycalix[4]arene with NaH and allylbromide in dry tetrahydrofuran, (4) Claissen rearrangement of 25, 26, 27, 28-tetrapropenyloxy- calix[4]arene, and (5) polymerization of tetra-p-propenyltetrahydroxycalix[4]arene to yield poly-tetra-p-propenyltetrahydroxycalix[4]arene. Analysis of products was performed using melting point analysis, FT-IR, and 1H NMR spectrometers. The yield of polymerization was 80.35% and m.p > 380 °C. Characterization of poly-tetra-p-propenyltetrahydroxycalix[4]arene was done using SEM and SAA. Structure of poly-tetra-p-propenyltetrahydroxycalix[4]arene was sparsely porous with crosslinked netty architectures, and possessed surface area of 46.572 m2/g. The application of poly-tetra-p-propenyltetrahydroxycalix[4]arene in the adsorption of Cd(II) cation had also been conducted. Adsorption parameters investigated included medium pH and contact time as well as adsorption isotherm. The resin could be applied as a good adsorbent in the adsorption of Cd(II) metal cation. The adsorption followed Langmuir isotherm model, where the measured adsorption capacity, adsorption constant (K), and adsorption energy were 8.5933 x 10-2 mmol/g, 485 L/mmol, and 32.653 KJ/mol, respectively.